CMOS-based Chebyshev current-mode ladder band-pass filter - Tiamsuphat, Aphinat; Prommee, Pipat (My University, 2015)
This paper presents a CMOS-based Chebyshev current-mode ladder band-pass filter (BPF). The integrator building blocks (lossy and lossless integrators) with 6 grounded capacitors are used to realize the BPF by using doubly terminated RLC ladder filter prototype based on TSMC 0.18μm CMOS technology. Frequency response of the circuit can be tuned between 1MHz and 200MHz through bias currents from 0.01 μA to 100 μA. The proposed circuit has many attractive features, for instant, low power supply as 1.5V, low dynamic power consumption and low Total Harmonic Distortion (THD). All simulation results are carried out by PSpice which are good agreements compared with the RLC prototype.
Keywords: Band-pass filter; Chebyshev; CMOS; High-frequency